PENGARUH PERTUMBUHAN JUMLAH USAHA MIKRO KECIL DAN MENENGAH TERHADAP PERTUMBUHAN EKONOMI KABUPATEN PELALAWAN DALAM PERSPEKTIF EKONOMI ISLAM - Landes Yuanda; Tara Shinta (LP2M STAI Imam Asy Syafii Pekanbaru, 2023)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the national economic growth, yet they face challenges such as capital constraints and a lack of quality management. This study analyzes the impact of MSME growth on the economic development in Pelalawan Regency, considering the perspective of Sharia economics. Using a mixed qualitative and quantitative descriptive approach, the data reveals that each 1 Rupiah increase in MSMEs can lead to a Rp60,278 growth in the economy. The Islamic economic perspective also has a significant impact on this relationship. The results of the determinism test indicate that 92.3% of economic growth is influenced by MSME growth, while other factors account for the remainder. Through hypothesis testing, there is evidence that the growth of MSMEs significantly affects the economic development of Pelalawan Regency, and the Sharia economic perspective also contributes significantly to this relationship. These findings provide insights for the government and industrial stakeholders to empower MSMEs in their economic development based on Sharia economic principles. Thus, collaborative efforts to overcome capital constraints, regulations, and market access can enhance the role of MSMEs in local economic growth.